Diagnóstico da Microbacia do Córrego Águas Claras, Juscimeira (MT), voltado à educação ambiental - Paula, Roselha Borges de (2016)
This research work includes the assessment of the Águas Claras stream watershed, focusing on the VERAH method, involving a group of students from the state school João Matheus Barbosa. For vegetation and habitat analysis maps of land use and vegetation cover and Permanent Preservation Area were elaborated. The erosive processes were interpreted with the application of the morphopedological approach. To characterize the types of residues accumulated in the watershed and to identify garbage disposal sites and domestic effluents, field surveys and interviews with the urban population and rural dwellers were carried out. Water quality was estimated through physical, chemical and microbiological analyzes of thirteen parameters, flow measurement and Water Quality Index (IQA) evaluation. It was observed that 84% of the watershed is occupied by pasture and temporary cropping activities, in which conservation practices of soil management and conservation are not adopted; 0.7% per permanent crop, consisting of jabuticaba fruit growing; 11.8% per urban area, where land use occurs disorganized with reduced vegetation cover, increased waterproofing rate, deficiencies in public infrastructure, lack of public policies and connivance of executive and legislative powers with undue acts of the population ; And only 3.5% of the watershed correspond to natural coverings of the soil, composed of areas of original or secondary native vegetation, remaining on the cliffs and slopes of the morrotes and on the banks of the watercourses, in which, disregarding the 78% of the ciliary vegetation of the stream was suppressed. The morphopedological map, with cartographic delimitation of homogeneous areas, shows eight compartments that presented medium to high susceptibility to laminar and linear erosion. Inadequate disposal of solid wastes and domestic effluents was verified, generating bad odors, attracting vectors of diseases, pollution and contamination of water. The data obtained in the water quality analyzes reveal that most of the samples were above the limits established by Resolution 357 of CONAMA. Of the nine analyzed variables that have limits established by said Law, six obtained results above that determined (E. coli - 80%, color - 83%, pH - 50%, phosphorus - 41%, BOD - 30% and OD - 8%). Only the samples of turbidity, nitrate and solids parameters were within the required standards. The IQA determination gave the water quality between reasonable (25%) and poor (75%), with reduction of upstream amount in the watercourse. The environmental education activities were carried out with the involvement, interest and participation of practically all the students. Through observation and analysis of the space they lived, they articulated theory and practice, identified and evaluated changes in the watershed, showing maturation during the course Of the work, which favored the expansion of knowledge, development of the critical spirit and changes of attitude.